2013
DOI: 10.1021/es303881h
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradability of Corexit 9500 and Dispersed South Louisiana Crude Oil at 5 and 25 °C

Abstract: The reported persistence of the dioctyl sodium sulfosuccinate (DOSS) surfactant in Corexit 9500 in the oil plumes formed during the Deepwater Horizon oil spill has contributed to concerns regarding the biodegradability and bioavailability of dispersed oil and dispersants used as an oil spill countermeasure in the Gulf of Mexico. We studied the biodegradation of DOSS and dispersed South Louisiana crude oil (SLC) in laboratory microcosms. Two oil-degrading cultures from the Gulf of Mexico were isolated, one from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 34 publications
9
95
2
Order By: Relevance
“…Biodegradation of anionic surfactant DOSS to α/β-ethyhexylsulfosuccinate (EHSS) occurs under aerobic conditions (37). In the dispersant-only treatment, a significant (P < 0.05) decrease (8%) of DOSS and an increase of EHSS (15%) was observed at T 3 (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Biodegradation of anionic surfactant DOSS to α/β-ethyhexylsulfosuccinate (EHSS) occurs under aerobic conditions (37). In the dispersant-only treatment, a significant (P < 0.05) decrease (8%) of DOSS and an increase of EHSS (15%) was observed at T 3 (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 More recently, an EPA group established that ethylhexyl sulfosuccinate (EHSS) monoesters are likewise obtained from the branched sulfosuccinate diester DOSS (1) during its biodegradation by oildegrading microorganisms found in the Gulf of Mexico. 5 As part of an ongoing effort to develop a trace analysis for surfactants and their degradation products associated with Corexit oil dispersants in Gulf of Mexico seawater field and laboratory microcosm samples, 6 we required access to stable isotope mass spectrometric standards of α-EHSS (2) and β-EHSS (3) for quantification of LC-MS/MS experiments. Herein, we report regioselective syntheses of quadruply labelled stable isotope mass spectrometric standards for α-EHSS ([ 13 C] 4 -2) and β-EHSS ([ 13 C] 4 -3) from [ 13 C] 4 -maleic anhydride (4) and prove the regiochemistry of both compounds by 13 C/ 13 C and 1 H/ 13 C NMR spectral correlation experiments.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study by Campo et al found that DOSS was biodegraded by 98% in 8 and ~38 days in cultures from surface and deep Gulf of Mexico waters (at 25°C and 5°C, respectively) (Campo et al, 2013). In the light of these findings it is important to monitor the DOSS and its degradation products in the environment as the released oil dispersant moves and transforms.…”
Section: Resultsmentioning
confidence: 99%
“…Despite of its low to moderate toxicity to most aquatic species (George-Ares and Clark, 2000;Hemmer et al, 2010;Judson et al, 2010) and skeptical biodegradation (Kujawinski et al, 2011;Campo et al, 2013), it increases the dissolution of polyaromatic hydrocarbons (PAHs, carcinogens) in aqueous phase (Barron et al, 2003). Moreover in presence of sunlight, a multifold (1.5-48) increase in the toxicity of DOSS dispersed oil was observed in eggs and larvae of Pacific herring (Barron et al, 2003).…”
Section: Significance Of Cecs In the Environmentmentioning
confidence: 99%
See 1 more Smart Citation